Hybrid Investigation of the Helical Blades of Savonius Wind Turbine in novel patent of lighting base - Mohammad Mohsen Peiravi; Arman Ashabi (Results in Engineering, 2022)
This study investigates the helical blades of a wind turbine as described in a recent patent for an independent lighting base. At four-time steps, the present work evaluated the displacement parameters, physical stress, and strain on the helical blades of a Savonius wind turbine, such as von mises stress, equivalent strain, first and third principal stress, and strain. Stresses are examined on the material, and this value is compared with the yield stress of the material in the finite element software of Autodesk Inventor Professional. According to the results, maximum and minimum values of von mises stress are 9.5987 MPa at the bottom of the helical blade and 9.9962E-5 MPa in the middle of the helical blade, respectively. Also, maximum and minimum values of equivalent strain are 12.3549E-5 at the bottom of the helical blade and 13.2388E-10 in the middle of the blade, respectively. Finally, maximum and minimum values of total displacement are 1.6792E-2 at time step 2 on top of the blade. Also, the minimum value of displacement is 1.2839E-5 at time step 1 at the bottom of the blade.